The indissolubility of marriage & the Council of Trent - Brugger, E. Christian (Catholic University of America Press, 2017)
Contents -- List of Tables in Appendix B -- Preface -- List of Abbreviations -- Introduction -- 1. The Errores of the Reformers -- 2. The Ritus of the Greeks -- 3. Indissolubility and the 1547 Bologna Sessions -- 4. Discussions at Trent on Marriage (1563) -- 5. Trent's Teaching on Indissolubility -- Appendix A. Authorities Referenced at Trent -- Appendix B. Recorded Statements of the General Congregation on Indissolubility from 1563 -- Appendix C. Schedule of the Council of Trent -- Selected Bibliography -- Index